(untitled) (Bangladesh Journal of Urology, 2020)
Background: Bladder cancer is the second most common cancer of the genitourinary tract. Mitomycin C has been commonly used in a perioperative fashion delivered intravesically immediately after TURBT Objective: To compare the results of post TURBT immediate single dose and multidose regimen of Mitomycin C therapy in the management of superficial transitional cell carcinoma of the urinary bladder. Method: The present prospective and comparative interventional study was conducted in the Department of Urology, National Institute of Kidney Diseases and Urology, Sher-E-Bangla Nagar, Dhaka from January 2015 to December 2016. Patients of superficial bladder cancer (tumor size ≤3 cm, number ≤3, grade I, II) were randomly included in the 2 groups. The sample size was seventy four (74). Thirty (30) patients were in each group and fourteen (14) were excluded from the study. In MMC single dose group (Group A), single dose of MMC 40mg/ 40ml was started immediately within 24 hours of TURBT. In MMC multi-dose group (Group B) 1st instillation of chemotherapy was started immediately within 24 hours of TURBT and additional instillation (5 instillations) were given as OPD basis and was continued weekly for 5 weeks. Follow-up was done on 3rd, 6th, 12th month of initial TURBT. Results: In this study mean age was 61.8±13.7 years in group A and 62.7±13.6 years in group B. Male was found 25 (83.3%) in group A and 26 (86.7%) in group B. Female was found 5 (16.7%) in group A and 4 (13.3%) in group B. Mean size of the tumor was found 2.13±0.78 cm in group A and 2.05±0.84 cm in group B. Mean number of tumor was found 1.8±0.8 in group A and 1.9±0.7 in group B. Tumor grade I was found 23 (76.7%) in group A and 25 (83.3%) in group B. Tumor status Ta of superficial bladder was found 25 (83.3%) in group A and 26 (86.7%) group B. Tumor status T1 of superficial bladder was found 5(16.7%) in group A and 4 (13.3%) group B. Five (16.7%) patients was found recurred in group A and 4 (13.3%) in group B at 6th month follow up. At 12th month follow up, 6 (20.0%) patients was found recurred in group A and 5 (16.7%) in group B. Side effect was found in 2 (6.7%) patients in group B and not found in group A. Conclusion: MMC single dose was similar to MMC multi-dose regimen with insignificant difference among the two. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.62-66